Interfaith Relation During Galungan Festival in Pengulon Village, Bali, Indonesia - Nazhmi Aulia Rahmania; Ghaniyyu Rahma Aurora Laksono Raharjo (PT Pro Panoramic Solution, 2025)
This research explores interfaith harmony in Pengulon Village, Buleleng Regency, Bali, which consists of three banjars: Tegalantang (majority Muslim), Bukit Sari, and Munduk Sari (majority Hindu). Using a qualitative approach, this research explores the tolerance that exists, especially when Galungan Day matches the preparation for the Prophet Muhammad's birthday. Data were obtained through interviews, observation, and documentation. The results showed that the Pengulon Village community was able to maintain harmony. Muslims can still carry out worship, recitation, and Maulid preparations calmly, while Hindus celebrate Galungan without obstacles. This tolerance is supported by mutual respect and good communication